"Bale maskowe" pracowników wirtualnych jako instrument rozmiękczania przestrzeni przedsiębiorstwa - Perechuda, Kazimierz (The Fancy Ball of the Virtual Workers as the Instrument of the Diffusion of the Enterprise Space, 2006)
In the paper the following issues are presented: the aim and functions of the virtual societies (virtual entities), the differences between virtual organizations, teams and virtual entities, the old and virtual business models, the assumptions of the motivation system for virtual entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 122-129